Prediksi Kebijakan Utang, Profitabilitas, Likuiditas, Ukuran, Dan Status Perusahaan Terhadap Kemungkinann Penentuan Peringkat Obligasi: Studi Empirik Pada Perusahaan Yang Menerbitkan Obligasi Di Bursa Efek Indonesia - Bram Hadianto; M. Sienly Veronica Wijaya (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2010)
The aim of this research is to know the prediction of debt policy, profitability, liquidity, size, and firm’s status on bond rating, and to find the accuracy rate for classifying companies that have investment grade of bond rating and non investment grade of bond rating based on these given factors. We employ logistic regression model as data analysis method. Our sample is taken fromIndonesian Bonds Market Directory (IBMD) in the year of 2008 which collected by purposive sampling method. There are 105 listed bond’s issuers until 2008. In our observation, there are 3 issuers that have no bond rating so that we use only 102 issuers as the sample. The results show that profitability is the only explanatory variable which has significant impact on bond rating with positive sign and the accuracy rate of debt policy, profitability, liquidity, size, and firm’s status to classify bond issuer category are as high as 85.3%.